1983
DOI: 10.1007/bf00541593
|View full text |Cite
|
Sign up to set email alerts
|

The use of ?Alternative treatments? by patients with rheumatoid arthritis

Abstract: In a study of 199 patients with rheumatoid arthritis, 68% were found to have tried 'alternative treatments'. Some treatments (acupuncture and faith healing) gave subjective benefit in nearly half those who tried them and were considered to be better than others (such as copper bracelets). No adverse reactions were reported. 'Alternative treatments' play an important role as self prescribed therapy in rheumatoid arthritis and their use should not be ignored nor underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Following the more recent interest in the use of CAM therapies in the population atlarge, a number of studies have focused on the use of CAM therapies by patients with specific medical problems. Research within this tradition has examined use of alternative therapies by patients with fibromyalgia, arthritis, cancer, and inflammatory bowel disease, to name but a few (Kronenfeld & Wasner 1982;Struthers et al 1983;Cronan et al 1989;Pioro-Boisset et al 1996;Nicassio et al 1997;Astin et al 1998;Ernst & Cassileth 1998;Rao et al 1999;Rawsthorne et al 1999;Lee et al 1995). These studies, however, do not address the prevalence of CAM use in the general population, our interest in this study.…”
Section: Use Of Cam Therapies In the Usamentioning
confidence: 88%
“…Following the more recent interest in the use of CAM therapies in the population atlarge, a number of studies have focused on the use of CAM therapies by patients with specific medical problems. Research within this tradition has examined use of alternative therapies by patients with fibromyalgia, arthritis, cancer, and inflammatory bowel disease, to name but a few (Kronenfeld & Wasner 1982;Struthers et al 1983;Cronan et al 1989;Pioro-Boisset et al 1996;Nicassio et al 1997;Astin et al 1998;Ernst & Cassileth 1998;Rao et al 1999;Rawsthorne et al 1999;Lee et al 1995). These studies, however, do not address the prevalence of CAM use in the general population, our interest in this study.…”
Section: Use Of Cam Therapies In the Usamentioning
confidence: 88%
“…Fourteen surveys of rheumatological patients' use of CM were identified [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Collectively they point to a high prevalence of CM use among this patient group, particularly in North America (Table 1).…”
Section: Patients' Use Of CMmentioning
confidence: 99%
“…Few surveys [11,13,14,18] have addressed the issue at all. The incidence of adverse events reported in these surveys is low; one report expressly states the total absence of adverse reactions [13].…”
Section: Patients' Use Of CMmentioning
confidence: 99%
“…A recent report by Kajiyama et al [13] showed that 23.3% of Japanese patients with RA in the cohort from the Tokyo metropolitan area used dietary supplements, the highest prevalence among all kinds of CAM they investigated. The prevalence of DS/HF use in those with rheumatic disorders, as reported by others [2][3][4][5][6][7][8][9][10][11]13], varied from 5% to more than 50%. Differences in the prevalence may be attributable to various factors, including the definition or classification of DS/HF, the survey methodology, respondent ethnicity or locality, and if patients went to clinics of general practitioners or specialists, etc.…”
Section: Introductionmentioning
confidence: 67%
“…It is not surprising, therefore, that many patients with RA decide to utilize various kinds of CAM, even though they are currently under a physician's care and are being treated with orthodox or conventional therapies for RA. In fact, previous reports concerning CAM use in patients with rheumatologic conditions which emerged from several countries and different ethnic groups demonstrated that 60-90% of patients have used CAM [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%